The Use of Terms and Signs of Handling Covid-19 on Government Agencies, Private, and Marine Attractions - Lilimiwirdi Lilimiwirdi; Astuti Pratiwi (Politeknik Negeri Padang, 2022)
The use of the term in handling covid-19 in government agencies, private, and tourist attractions and the public will accelerate the way of people in adapting to covid-19. The theories used are words, diction, sentences, discourses, semiotics, semantics, and ideologies. The research used the listening method. Data collection was done by inserting data in the form of terms and signs of covid-19 used in government, private, marine attractions in Padang City and Pesisir Selatan Regency. The data was collected through interviews and questionnaires with 150 informants. The use of terms and signs in the handling of covid-19 is commonly used in Indonesian, English, and Minangkabau languages, such as in the form of words, phrases, clauses, sentences, abbreviations, acronyms, and other preventive signs. Later, these posters and slogans were made in three languages, namely Indonesian, English, and Minangkabau. The use of signs and images on these posters and slogans is to clarify the description. The use of terms and signs is used by informants in government agencies, private, and tourist attractions so as to speed up the interaction with the environment. Whenever the people already know about the science of viruses and the rules of interactions in the environment, it will help to accelerate the economic growth and tourism.